A dual indicator approach for monitoring benthic impacts from organic enrichment with test application near Atlantic salmon farms. Issue 1 (15th November 2017) - Cranford, Peter J.; Brager, Lindsay; Wong, David
Abstract: The organic enrichment of surficial sediments has a known effect on benthic faunal communities due largely to oxygen depletion and sulfide toxicity. Total dissolved sulfide (free S − 2  = H2 S + HS −  + S 2 − ) concentrations in sediments are widely measured as a practical indicator of community effects. However, the standard ion selective electrode (ISE) method for free S − 2 analysis can provide biased results owing to the inclusion of non-toxic mineral sulfides and the oxidation and volatilization of free S − 2 . A rapid field protocol was developed that alleviates these problems while also providing data on dissolved oxygen concentrations. Sediments collected near salmon aquaculture pens over cohesive and permeable substrates were analysed using the standard and new protocols. The results confirm previous conclusions of artifacts with the standard ISE method, while the dual indicator approach more accurately describes the stages, spatial extent and magnitude of sediment geochemical alterations affecting benthic communities. Highlights: A rapid field protocol was developed and validated for monitoring the organic enrichment status of marine sediments. UV spectrophotometric analysis of total free sulfides in porewater resolved errors inherent with the analysis of sediment/water slurries. Dissolved sulfide and O2 monitoring describes the stages, spatial extent and magnitude of benthic community effects from organic enrichment. Test application of the methods at salmon farms indicate a localized effects in cohesive sediments, and far-field effects in coarse sediments.